Evaluasi Produktivitas Crushing Plant Untuk Pencapaian Target produksi 30.000 Ton/Bulan Batu Granit PT Mandiri Karya Makmur Di Desa Tanjung Gunung Kabupaten Bangka Tengah: Evaluation Of Crushing Plant Productivity To Meet Production 30.000 Ton/Month Of PT Mandiri Karya Makmur’s Granit Rock In Tanjung Gunung Village, Central Bangka Regency - Firmansyah, Firmansyah; Tono, E.P.S.B Taman; Pitulima, Janiar (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2017)
PT Mandiri Karya Makmur is one of private company that engaged in sector of mining and processing of granite rock located in Tanjung Gunung village, Central Bangka Regency with production target of 30.000 ton/year. PT MKM operates 1 unit of crushing plant as a place of granite rock crushing process in order to produce the size of granite rock product that suit to consumer demand. However, The production target of determined crushing plant had not been reached.The aim of this research was to assess the real productivity of crushing plant of PT MKM. The data used in in this research included work time data, the amount of obstructive production time, weight of rock sample and belt conveyor velocity. The Data had functions to assess the availability of equipment and the real productivity of crushing plant. It recommended to repair crushing plant in order to increase the productivity from the result of calculation data.The result of crushing plant analysis in field showed that installed production equipment was 56.250 ton/month, 18.738 ton/month of maximal production, and the real crushing production achieved of 8.848,5ton/month.The availability value of crushing unit, mechanical availability (MA) was 62.5 %, phisycal availability (PA) 71.66 %, use o availability (UA) 65.89 %, effective utilization (Eut) 47.22 %, effective work time 4.25 hour/day and work efficiency 47.22 %. From the condition, production target had not been achieved. The efforts can be conducted to repair crushing unit in order to meet production target such as : 1) To change production target to 15.000 ton/month, 2) To decrease delay time caused human errors (non technical) will raise effective work time from 4.25 hour/day to 6.45 hour/day and will raise productivity as big as 4.580,5 ton/month, from 8.848,5 ton/month to 13.429 ton/month, 3) To change crushing plant